Factors associated with therapy non-completion for children with problematic sexual behaviors - Pitre, Camille; Daignault, Isabelle; Chouinard Thivierge, Stéphanie; Tourigny, Marc (Frontiers in Child and Adolescent Psychiatry, 2024)
This research project was made possible thanks to the voluntary participation of several children with problematic sexual behaviors (PSB) receiving services from a specialized center as well as their caregivers. We would like to thank these children and their caregivers for contributing to the advancement of knowledge on PSB and to the improvement of clinical services. We would also like to thank Manon Robichaud who participated in the design of the database used for this project. Finally, this research project is part of a series of projects of the Marie-Vincent Interuniversity Research Chair on sexual assault against children. This Research Chair is subsidized by the Marie-Vincent Foundation.